Perizinan Terhadap Adaptasi Bangunan Warisan Budaya Tjan Bian Thiong Di Kota Yogyakarta - Sumiarni, M. G. Endang; Pudyatmoko, Y. Sri; Sharaningtyas, Yustina Niken (UI Scholars Hub, 2020)
This study aims to find out and examine licensing for the adaptation of the Bian Thiong Tjan Cultural Heritage Building in the city of Yogyakarta as well as to assess the background of permits granted even though the adaptation of buildings is contrary to the basic principles of preservation of Cultural Heritage Buildings. The results of the study were permits for the adaptation of the Bian Thiong Tjan Cultural Heritage Building in the city of Yogyakarta, not a permit to adapt but to apply for a building permit to establish a new building in the form of a hotel.